Analysis of the Effect of Intellectual Capital on Financial Performance, Revenue Growth, and Value of Manufacturing Companies on the Indonesia Stock Exchange 2016-2019 - Umboh, Friscilla Fabiola; Dian Masita Dewi (HM Publisher, 2022)
The concept of intellectual capital has a goal that leads to the control and management of the company (Mouritsen et al., 2001) with the perspective of improving organizational performance, creating a competitive advantage of the company (Khalique et al., 2011) which can differentiate itself from competitors in today's modern economic era (Bhasin, 2008) which also leads to long-term profits (Jordão & de Almeida, 2017). The measurement of the impact of intellectual capital management that is most widely used is developed by (Pulic, 1998), VAICTM (Value Added Intellectual Coefficient) to measure the extent to which the company generates an added value based on the efficiency of intellectual capital that is supported and influenced by the relationship between value-added to physical capital, human capital and structural capital. This research is causal research that aims to analyze the causal relationship between the independent variable and the dependent variable. The independent variable in this study is intellectual capital as measured by the Value-Added Intellectual Coefficient (VAICTM) which is the sum of three influential resources, namely Value-Added Human Capital (VAHU), Value Added Capital Employee (VACA), and Structural Capital Value Added (STVA). The dependent variable in this study is the company's performance as measured by Return on Assets (ROA), company growth is measured by Growth Revenue, and company value is measured by Tobin's Q. Based on the results of the study, it can be concluded that intellectual capital has no significant positive effect on the company's financial performance. manufacturing on the Indonesia Stock Exchange in 2016-2019, because the manufacturing industry is included in the category of low-IC intensive industries (not dense intellectual capital) where operational activities are still dominated by the use of many fixed assets compared to intellectual capital and initial management of intellectual capital which is still considered as costs and have not shown results that affect the company's financial performance.